MEMBERDAYAKAN KELUARGA DENGAN PENDEKATAN PENDIDIKAN DI MASJID NURUL HUDA DUSUN TENGOROREJO DESA SONGGON KECAMATAN SONGGON KABUPATEN BANYUWANGI - Atiqatul Musyarofah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2019)
Mosques are one of the places of worship for Muslims, but mosques are also a means of building excellent personal formation. Inside the mosque, the beginning of the civilization of Muslims began, but in the view of the community, the mosque only functioned as a place of worship even though there was a lot that was usually done through the mosque's media. Mosques can be the center of civilization and human development, it is through mosques that we are educated by the Prophet Muhammad to become qualified human beings. The type of data collected is primary data. Primary data is a variety of data and information obtained directly from informants and recommendations in the field that are administrators of takmir and from village officials. The data collected is related to the goals and objectives of the activity, such as reports and documents regarding the empowerment of education by families and communities obtained from community leaders. Mosque-based Posdaya Thematic KKN is carried out according to a predetermined schedule with systematic stages. The stages begin in the first week and the following weeks according to schedule.